Pengaruh Fear Of Missing Out (FOMO), Shopping Enjoyment dan Hedonic Shopping Motivation Terhadap Online Impulse Buying (Studi pada Gen Z pengguna E-Commerce Shopee di Purworejo) - Ramadhani, Sania Rizki; Ekowati, Titin; Rahmawati, Fitri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The growth of e-commerce in Indonesia, particularly through Shopee, has driven changes in consumer behavior, especially among Generation Z, who are quick to adapt to technology and highly active on social media. These conditions make Gen Z more susceptible to emotional triggers and impulsive purchasing tendencies in digital environments. The population in this study consists of all residents of Purworejo. The sample was determined using a purposive sampling technique, resulting in 120 respondents. Data were collected using a questionnaire distributed via Google Forms. Data analysis was carried out using SPSS for Windows. The questionnaire used in this research was pilot-tested and met the required standards of validity and reliability. Hypothesis testing was conducted using multiple linear regression analysis. The findings indicate that (1) fear of missing out (FoMO) has a positive and significant effect on online impulse buying; (2) shopping enjoyment has a positive and significant effect on online impulse buying; and (3) hedonic shopping motivation has a positive and significant effect on online impulse buying.